A History of India for Children - Dalal, Roshen (New Delhi Puffin Books, 1977)
Spanning the ages from Indus Valley Civilization of 2500 BC to the triumph of Independence in 1947, the important personalities and events are vividly described.
Keywords: India -- History -- Juvenile literature